2019
DOI: 10.1097/rli.0000000000000533
|View full text |Cite
|
Sign up to set email alerts
|

Glymphatic Pathway of Gadolinium-Based Contrast Agents Through the Brain

Abstract: Background: The "glymphatic system" (GS), a brain-wide network of cerebrospinal fluid microcirculation, supplies a pathway through and out of the central nervous system (CNS); malfunction of the system is implicated in a variety of neurological disorders. In this exploratory study, we analyzed the potential of a new imaging approach that we coined delayed T2-weighted gadolinium-enhanced imaging to visualize the GS in vivo. Methods: Heavily T2-weighted fluid-attenuated inversion recovery (hT2w-FLAIR) magnetic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
106
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(112 citation statements)
references
References 35 publications
2
106
2
2
Order By: Relevance
“…From the continuity equation (expressing conservation of mass), we know that this net flow must continue in some form through other parts of the system (e.g., along perivascular spaces around penetrating arteries, arterioles, capillaries, venules). This is supported by recent magnetic resonance imaging studies in humans that have demonstrated that CSF tracers are transported deeply into the brain via perivascular spaces [911].…”
Section: Introductionmentioning
confidence: 73%
“…From the continuity equation (expressing conservation of mass), we know that this net flow must continue in some form through other parts of the system (e.g., along perivascular spaces around penetrating arteries, arterioles, capillaries, venules). This is supported by recent magnetic resonance imaging studies in humans that have demonstrated that CSF tracers are transported deeply into the brain via perivascular spaces [911].…”
Section: Introductionmentioning
confidence: 73%
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Furthermore, various pathologic and nonpathologic states are now known to result in brain parenchymal signal intensity changes on unenhanced T1WI, including gadolinium deposition. [21][22][23][24][25][26][27][28][29][30] Chronologic signal intensity changes on T1WI and myelination patterns within the cortex and subcortical white matter, corpus collosum, and various white matter tracts within the supratentorial and infratentorial brain have been well-characterized in pediatric and adult populations. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]19,20 However, agedependent T1WI signal intensity alterations within the deep gray nuclei, cerebellar nuclei, and brain ...…”
mentioning
confidence: 99%
“…Contrast-based studies carried out in rodents 13 , non-human primates 23 , and human subjects 3739 demonstrate CSF from cisternal compartments travels along perivascular spaces surrounding leptomeningeal vessels and enters the brain along perivascular spaces surrounding penetrating vessels (also termed Virchow-Robin spaces). From here, solutes such as fluorescent tracers or gadolinium-based MRI contrast agents that do not cross the blood brain barrier and are not taken up by astrocytes exchange into the brain interstitium via gaps between overlapping perivascular astroglial endfoot processes.…”
Section: Resultsmentioning
confidence: 99%